Management of Water Resources in the Semiarid Region of Rio Grande do Norte: a case study on the municipality of Lucrécia - Oliveira, Marlene Yara Tenório Soares de; Silva, Marcia Regina Farias da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
This research aimed to identify water resources management strategies in extreme drought event scenarios in the municipality of Lucrécia, in the state of Rio Grande do Norte (RN), in the period 2012 to 2018. As a methodological procedure, a bibliographical and documentary, in addition to field research, with interviews with municipal managers and residents. A photographic record of the study area was also carried out. It was found that, in the city, there is a folder dedicated to water resources that guides water management and is the basis for the adoption of measures aimed at municipal supply in times of difficult access to water, due to the reduction in water availability. It was observed that part of the interviewed population understands the drought as responsible for the difficulties faced in the city, mainly about the reduction of the water level in the reservoir. It was found that, of the 52 towns belonging to the hydrographic basin of the Apodi-Mossoró river, only 10 participate in the meetings of the basin committee, the municipality of Lucrécia does not have representatives on the Committee. This finding deserves special consideration since water and the administration of its multiple applications are generators of conflicts, it highlights the importance of understanding how municipalities in the Semiarid region carry out the management of water resources and how they understand the challenges of coexistence with its area, aiming at the sustainable use of water.